Lessons we learned from the COVID-19 outbreak - Kamruddin Ahmed (Universiti Malaysia Sabah, 2021)
The emergence of coronavirus disease 2019 (COVID-19) did not only cause a devastating effect on every corner of society but also taught us many important lessons. One of the lessons is on the importance of the principles of public health. We have seen this repeatedly in recent years during the emergence of SARS, Ebola, MARS and Nipah (Ahmed et al., 2019). The principles of public health have been effective in controlling these infections and we are confident that COVID-19 will be under control using these simple measures. As health professionals, we must set examples by following preventive measures, i.e. wearing mask properly, safe distancing and washing hands, to prevent and control the spread of COVID-19. Unfortunately, there is an erroneous concept in these measures however, therefore, cooperation of everybody in the community is necessary to overcome them.